The role of ultrasonography of the brachiocephalic arteries in the diagnosis of atherosclerosis in women - Aleksandra S. Moskvicheva; David R. Davidov (LLC "MEDIAFORMAT", 2023)
Atherosclerosis is a common cause of ischemic injury of the brain tissue and myocardium. Over time, pathogenesis of atherosclerosis was considered through the prism of the increase in blood levels of lipids forming atherosclerotic plaques on the vascular walls under favorable conditions. However, recently, many studies turned to search for additional factors: different contributions of the lipid profile components, vascular endothelium, inflammation, and hormonal status to the process were reported. Ultrasonography remains the routine method for vascular screening for many years, it also helps to control the development of atherosclerosis. The reported clinical case shows an exceptional role of ultrasonography and uncovers some features of performing ultrasonography for non-experts in the diagnosis of atherosclerotic vascular lesion.